EVALUATION OF ECONOMICS LEARNING AT SMA NEGERI 6 PADANG THROUGH THE IMPLEMENTATION OF AUTHENTIC ASSESSMENT ON STUDENTS’ LEARNING OUTCOMES - Widya Astutii; Irman Irman; Dessyta Gumanti (Ikatan Dosen Menulis, 2025)
This study aims to evaluate the implementation of authentic assessment in economics learning at SMA Negeri 6 Padang and to analyze its impact on students’ learning outcomes. The research employed a descriptive qualitative approach with a case study design. The research subjects consisted of one economics teacher and 30 students of class XI IPS. Data were collected through participatory observation, in-depth interviews, and documentation of learning instruments. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques. The findings indicate that the teacher has implemented authentic assessment covering attitudes, knowledge, and skills; however, the implementation has not been optimal due to time constraints, the dominance of cognitive-based tests, and the incomplete development of assessment rubrics. Project-based and portfolio assessments were found to increase students’ engagement, understanding of economic concepts, and learning outcomes. This study recommends strengthening teachers’ competencies in developing authentic assessment instruments to improve the effectiveness and sustainability of economics learning evaluation.